Driver para acionamento de luminárias LEDs residenciais com o uso do comando auto-oscilante e regulação da corrente de carga - Kohler, Samuel Valerio (2020)
This work presentsthe development of a driver circuit for LEDs with residential application using static convertersfor a 26,636 W load.The driver providesthenecessary characteristics for the LEDs good operation, and adequate the equipmentto the standardsrelated to energy quality (IEC61000-3-2 Class C and NBR 16026:2012). The system utilizesthe two-stagestrategy where are used a SEPIC converter operating in discontinuous currentconduction mode for power factor correction and an inverter with LC resonant filter for power control. The switches of both stages are controlled by the self-oscillating command. A bus voltage regulation circuit is added to compensate variations in the supply voltage and secure a constant value to the LEDs current. The design methodologies are presented for each part of the system, and thedesign is presented. Practical results are obtained through a prototypebased in the design realized in order to demonstrate the proposed topology operation. The prototype was tested with a mains voltage variation off 110 V to 135V. The driver comply with the IEC61000-3-2 Class C for all the voltage range. The power factor is superior to0.97 and the LEDs current ripple is inferior 10 %, in complianceto practical recommendation 1 of the IEEE Std. 1789-2015. The bus voltage regulation circuitachieved a reduction in variation of the LEDs current mean value of 40.19 % to 4.74 % when compared to the driver operating without the regulator.